Alite hydration mechanism in presence of ye’elimite related to BAY cements - Londono-Zuluaga, Diana; Tobón, Jorge Iván; García-Aranda, Miguel Ángel; Santacruz-Cruz, María Isabel; Gómez-de-la-Torre, María de los Ángeles (My University, 2019)
One alternative to decrease CO2 emissions from ordinary Portland Cement (OPC) production consists on the development of a new kind of eco-cements composed by less calcite demanding phases. That is the case of Belite-Ye’elimite-Ferrite (BYF) cements, which have β-belite as a main phase and ye’elimite as a secondary phase. But the low reactivity of β-belite is well known, consequently these materials develop low mechanical strengths at early/intermediate hydration ages. A possible solution proposed to solve this problem consists on the production of cements which contain belite, alite and ye'elimite together, known as Belite-Alite-Ye’elimite (BAY) cements. Consequently, the reaction of alite and ye'elimite with water would develop cements with higher mechanical strengths at early ages, while β- belite will contribute to later ages. The main objective of this work is to better understand the hydration behavior of monoclinic alite in presence of ye’elimite (both stoichiometric and pseudo-cubic polymorphs), in order to be compared with a BAY eco-cement systems. The hydration of systems with selected alite/ye’elimite ratios were studied for the first 24 hours. The main techniques used for this study were in-situ synchrotron X-ray powder diffraction combined with Rietveld methodology and isothermal calorimetry.
Keywords: Cemento; Eco-cement; Calcium sulfoaluminate cement